2019
DOI: 10.1103/physrevb.99.024305
|View full text |Cite
|
Sign up to set email alerts
|

1/f flux noise in low- Tc SQUIDs due to superparamagnetic phase transitions in defect clusters

Abstract: It is shown here that 1/f α flux noise in conventional low-Tc SQUIDs is a result of low temperature superparamagnetic phase transitions in small clusters of strongly correlated color center defects. The spins in each cluster interact via long-range ferromagnetic interactions. Due to its small size, the cluster behaves like a randomtelegraphic macro-spin when transitioning to the superparamagnetic phase. This results in 1/f α noise when ensemble averaged over a random distribution of clusters. This model is sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 100 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…In solid-state qubits and quantum circuits, these environmental fluctuators spoil the coherence of the fragile quantum states, thus impeding the progress toward large-scale quantum computing. Although the underlying mechanism is still a matter of wide debate (2,(9)(10)(11)(12)(13)(14), surface paramagnetic centers are omnipresent and are considered to be a major contributor to this decoherence. The noise that they induce is largely independent of the specific metals used to fabricate the devices (15), and their surface density in quantum devices (1-3, 11, 16-18) is remarkably constant at about 10 17 m −2 .…”
Section: Introductionmentioning
confidence: 99%
“…In solid-state qubits and quantum circuits, these environmental fluctuators spoil the coherence of the fragile quantum states, thus impeding the progress toward large-scale quantum computing. Although the underlying mechanism is still a matter of wide debate (2,(9)(10)(11)(12)(13)(14), surface paramagnetic centers are omnipresent and are considered to be a major contributor to this decoherence. The noise that they induce is largely independent of the specific metals used to fabricate the devices (15), and their surface density in quantum devices (1-3, 11, 16-18) is remarkably constant at about 10 17 m −2 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Faoro et al attempted to explain this noise via dynamics of the spins that are strongly-coupled by the Ruderman–Kittel–Kasuya–Yosida (RKKY) interactions at the superconductor–insulator interface 21 , 22 . In what follows, the RKKY interactions were also adopted in the spin-cluster model by De 23 . Yet another proposal by Wu and Yu suggested that the noise emerges from the hyperfine interactions of the relaxing surface spins 24 .…”
Section: Introductionmentioning
confidence: 99%
“…3a]. It has been suggested that clusters of spins may act as "macrospins" with effective magnetic moments and relaxation processes, which produce an ensemble of telegraphic noise processes giving rise to 1/f noise [42,43,46]. Assuming the effective relaxation rate of a cluster rapidly decreases with the number of spins in the cluster [42], an increasing size with applied field would be consistent with the rise in low-frequency flux noise.…”
mentioning
confidence: 99%